Speaker Verification Using Hybrid Scheme for Arabic Speech - Moharom ed, H.R (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work , a hybrid scheme tor Arabic speech for the recognitionof  the speaker  verification  is presented  . The scheme is hybrid as utilizes the traditional digi tal signal processi ng and neural network . Kohonen neural  network has been used as a recognizer  tor speaker verification after extract spectral  features from an acoustic signal  by Fast Fourier Transformation Algorithm(FFT) .The system was im plemented using a PENTIUM  processor , I000MHZ compatible and MS-dos 6.2 .